2015
DOI: 10.5352/jls.2015.25.5.496
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Temperature on Maintaining the Stability of Water Quality in Biofloc-based Zero-water Exchange Culture Tanks

Abstract: This study explored adequate water temperature ranges for maintaining stable water quality in a biofloc-based zero-water exchange culture system. Five experimental tanks with the following temperatures were set up: 10℃, 15℃, 20℃, 25℃, and 30℃. First, a biofloc-based culture system was developed in the experimental tanks; then, the tanks were stocked with goldfish and went without a water exchange for 60 days. Conditions for developing a biofloc-based culture system and stable water quality in low concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…In a study conducted on goldfish, different temperature values were compared and it was reported that the survival rate and growth rate were significantly lower at 10 and 15°C. In addition, ammonium nitrogen was observed to be higher at low temperatures (Cho et al, 2015). The highest survival rate, growth performance and water quality were observed at 25 and 30°C temperatures.…”
Section: Sensitivity Of Water Temperaturementioning
confidence: 90%
“…In a study conducted on goldfish, different temperature values were compared and it was reported that the survival rate and growth rate were significantly lower at 10 and 15°C. In addition, ammonium nitrogen was observed to be higher at low temperatures (Cho et al, 2015). The highest survival rate, growth performance and water quality were observed at 25 and 30°C temperatures.…”
Section: Sensitivity Of Water Temperaturementioning
confidence: 90%
“…Furthermore, the introduction of a RAS for high density and rapid growth of eel may cause an increase in infrastructure costs. Eel is cultured at the range of water temperature of 25℃-30℃ throughout the year, therefore, it is applicable to the BFT aquaculture (Cho et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…According to the research findings that composting of aquaculture effluents as agricultural recycling includes many organic matters such as nitrogen and phosphorus in the fish excretions (Kim et al, 2016a), aquaculture effluent perceived as a water pollution source (Lee, 2001;Subramaniam et al, 1994) can be used as a concept of a virtuous cycle of resources. The aquaculture effluent used in this study was discharged from a farm that applied biofloc technology (BFT), which is an eco-friendly farming technique that reduces water pollution by removing excess organic nitrogen in fish excretions and remaining fertilizers using biofloc in the water treatment process of the farm (Cho et al, 2015). In particular, effluents from inland water culture applying BFT contain organic nitrogen or phosphorus necessary for plant growth, and thus can be used as a useful resource in cultivating crops (Kim et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%